Recurrent fatal necrotizing fasciitis due to Streptococcus pyogenes in a child with hereditary sensory and automic neuropathy type IV - (:unkn) unknown (My University, 2011)
Although necrotizing fasciitis (NF) is a rapidly progressive infection, recurrent NF is very rare. Herein we report a rare case of recurrent NF due to Streptococcus pyogenes. A 12-year-old female with hereditary sensory and autonomic neuropathy (HSAN) type IV presented with fever and swelling on her left knee. NF was diagnosed and she was treated successfully. Two years later she was readmitted with NF of the right knee and limb. Despite treatment, progressive tissue necrosis developed and proximal femur amputation was performed. Eight months following the second attack she was readmitted with NF of her left knee and her entire leg. Despite a wide surgical debridement and antibiotic treatment, the clinical status of the patient failed to improve and she subsequently died. Although many conditions have been reported to be predisposing factors for NF, this is the first report of an association between HSAN type IV and recurrent NF due to S. pyogenes. We recommend antibiotic prophylaxis for patients with NF due to S. pyogenes, especially for those with predisposing factors.
Keywords: Female; Humans; Child; Streptococcal Infections; Anti-Bacterial Agents; Recurrence; Streptococcus pyogenes; Amputation; Debridement; Fasciitis, Necrotizing; Fatal Outcome; Hereditary Sensory and Autonomic Neuropathies